Analysis of Nationalism in Kurikulum Merdeka - Gupi Rohman Nurmansyah (Inovasi Kurikulum, 2023)
Nationalism is related to problems related to many people in a nation and country, such as corruption, radicalism, discrimination, and racism in culture. The concept of nationalism, according to experts from different countries, is almost entirely the same, as differences will not make a problem. Especially in Indonesia, the concept of nationalism has a critical position, even entering the realm of education. The Kurikulum Merdeka emphasizes Profil Pelajar Pancasila, who follows all the precepts in their design on the competence of graduates, but whether the five precepts are already in the mapping of the Kurikulum Merdeka needs to be carried out in-depth analysis. This research uses a qualitative approach to the literature study, which analyzes the Kurikulum Merdeka on Profil Pelajar Pancasila. The result is that the third precept, namely "Unity of Indonesia", which has the concept of nationalism, has not yet fully emerged comprehensively. So, it is necessary to map the concept of nationalism related to the material to the strategy, especially on the idea of the third precept, namely "Unity of Indonesia" in all disciplines of study for students. AbstrakNasionalisme dianggap berhubungan terhadap permasalahan yang berkaitan dengan banyak orang pada sebuah bangsa maupun negara seperti korupsi, radikalisme, diskriminasi, rasisme hingga budaya. Konsep nasionalisme menurut para ahli dan dari berbagai negara hampir sepenuhnya sama, adapun perbedaan tidak akan membuat sebuah permasalahan. Khususnya Indonesia konsep nasionalisme memiliki kedudukan yang sangat penting, bahkan masuk dalam ranah pendidikan. Kurikulum merdeka yang menekankan profil pelajar Pancasila yang mengadopsi semua sila dalam desainnya pada kompetensi lulusan, namun apakah ke lima sila sudah ada dalam pemetaan kurikulum merdeka perlu dilakukan analisis yang mendalam. Penelitian ini menggunakan pendekatan kualitatif studi pustaka, yang menganalisis kurikulum merdeka pada profil pelajar Pancasila. Hasilnya bahwa, sila ke-tiga yaitu “Persatuan Indonesia” yang terdapat konsep nasionalisme di dalamnya belum sepenuhnya muncul secara komprehensif. Sehingga perlu adanya pemetaan konsep nasionalisme terkait materi hingga strateginya khususnya pada konsep sila ke-tiga yaitu “Persatuan Indonesia” pada semua disiplin kajian untuk siswa.Kata Kunci: Kurikulum; Kurikulum Merdeka; nasionalisme; Profil Pelajar Pancasila